DESIGNING A TEACHER TRAINING PROGRAMME FOR CHARACTER EDUCATION: AN INTERNATIONAL PARTNERSHIP - Fernández González, Manuel Joaquín; Pigozne, Tamara; Verdeja Muñiz, María; Säre, Egle; Surikova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
There is a need of innovative teacher training programmes for character education. This paper addresses three research questions: What are the challenges that a teacher training programme for character education should address? What are the learning outcomes that the programme should achieve? How should the programme be structured for supporting the achievement of those learning outcomes? Two regional authorities, three schools, three universities and a centre of teacher training from Latvia, Estonia and Spain created a strategic partnership for answering these research questions, using design-based implementation research. The results include six domains of learning outcomes and a programme structure adaptable to different educational context.